TEXTILE PRODUCT DELIVERY SYSTEM IN PT. WINNERTEX - Wiwik Kuntarsih; Yuce Yuliani, Skom, MM (Jurnal Sistem Informasi, 2000)
Delivery of goods is done at company PT. Winnertex if traced further can be knownclearly that the sending process is still too manual done once, this can be evidencedby the process of making the road by the customer a letter to the manager who had togo through the part - a part that should not have passed if the delivery of goodsalready conducted a computerized system.Therefore, it is necessary to discuss again the process of making a pass that must bepassed by the customer. In order for delivery of goods can be done quickly andaccurately.